Heuristic analysis of structure, activity and selectivity relationships of isocoumarin derivatives as potential antifungal agents - Erić, Slavica; Simić, Milena (Archives of Pharmacy, 2024)
A series of recently synthetized and biologically evaluated isocoumarin derivatives (n=16, including voriconazole as standard) were used for heuristic analysis of structure, activity and selectivity relationships. While research of isocoumarins found in the literature was mainly focused on antifungal properties of 3-alkyl/aryl compounds, this study used structures synthetized by a strategy merging antifungal properties of isocoumarins with some known fungal pharmacophores. Rationalization of activity and selectivity was performed using the results of testing against C. albicans (CA) and testing on a normal human lung fibroblast cell line (MRC5). Structures were created and optimized using the ChemDraw Ultra 8.0 and MOPAC software. Calculation of molecular descriptors and the heuristic method, using the Codessa software, were applied for the selection of the most significant descriptors for activity against CA, as well as selectivity against CA versus MRC5. Biological tests for determination of activity against CA used in studies include inhibition of hyphal growth, so the activity against resistant cells was also considered. The supposed mechanisms of action, including lacton opening and electrophilic attack on nucleophiles, as well as inhibition of lanosterol 14a-demethylase (CYP51), were in agreement with the results obtained. The results could serve as a basis for further optimization of isocoumarin derivatives with respect to better activity, selectivity and action against resistant species.